Triple Helix and the evolution of ecosystems of innovation: The case of Silicon Valley - Josep M. Pique; Jasmina Berbegal-Mirabent; Henry Etzkowitz (Triple Helix, 2018)
Silicon Valley's innovation ecosystem has evolved in the last decade. In this study we aim to understand how and why Silicon Valley evolves by identifying changes on the role played by the Triple Helix Agents. We also aim at identifying if changes in one of the agents trigger evolution of the others. Taking the startup as the unit of analysis and applying a multiple case-study approach, the results are analyzed on the bases of the Triple Helix Model and interpreted in the light of the periods of development of an entrepreneurial venture. Our findings suggest that the role of the Triple Helix agents evolves over time and therefore, so does an innovative ecosystem. Main changes refer to the (1) rise of accelerator programs as a new player in the ecosystem; (2) an early engagement of corporations with startups; (3) the geographical expansion of Silicon Valley, now including San Francisco; (4) an increasing commitment of universities with capital funds; and (5) the rise of micro-multinationals due to talent shortage and fierce competition in the area.
Keywords: 330; Silicon Valley; Innovation ecosystems; Triple Helix; Evolution; Startup